2013
DOI: 10.1007/s00167-013-2401-7
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic double-row cuff repair with suture-bridging: a structural and functional comparison of two techniques

Abstract: A prospective, non-randomized, comparative study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 33 publications
2
69
1
Order By: Relevance
“…Our results in terms of pain relief, ROM and clinical scores are in accordance with those of previous studies reporting RCR by suture bridging. [15,16] However, we did not observe any statistical differences between the groups in terms of clinical outcomes and re-tear rates.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Our results in terms of pain relief, ROM and clinical scores are in accordance with those of previous studies reporting RCR by suture bridging. [15,16] However, we did not observe any statistical differences between the groups in terms of clinical outcomes and re-tear rates.…”
Section: Discussioncontrasting
confidence: 68%
“…The number of patients with medial cuff re-tears (n=5) in our study was too small to allow for definitive conclusions. Boyer et al [15] compared the results of 38 shoulders which were repaired by the knotted suture bridging technique to 35 shoulders repaired with knotless bridging with suture tape material. In terms of structural outcomes, the authors found a lower re-tear rate with the knotless tape-bridging construct, which was insignificant.…”
Section: Discussionmentioning
confidence: 99%
“…Vaishnav and Millett 60 demonstrated excellent results in a series of seventeen patients treated with a knotless transosseous-equivalent technique. However, studies by Boyer et al 61 and Rhee et al 62 both found higher magnetic resonance imaging (MRI)-proven retear rates in their knotless groups compared with their knotted groups. Despite the increase in retears in the knotless groups, there were no differences in clinical outcomes between either cohort in either study.…”
Section: Current Techniquesmentioning
confidence: 99%
“…It has been biomechanically shown to have a higher tendon-bone contact area, a higher tendon-bone contact pressure, and a higher load to failure than conventional DR. [20][21][22] In addition, numerous clinical studies have shown excellent clinical results with the SB technique. [23][24][25][26] Reported retear rates using the SB technique range from 0% for small and medium tears to 42% for large and massive tears, 7,27 but it is unknown how these rates compare with conventional DR or SR techniques. In a Level I study, Gartsman et al 28 showed a significantly lower retear rate in patients using the SB technique compared with an SR technique.…”
mentioning
confidence: 99%